The use of treatment wastewater in the desert land culture in AL-Ramadi City - Abdul Hadi Al- Rawi, Ali; Mohammad Karim, Bassim; Eyada Khudhair, Ahmed (Journal of Planner and Development, 2016)
Field study was done to examine and test the suitability of the wastewater and the possibilityof use it as irrigation water in the desert land culture in Al-Ramadi city, thus reducing pollution in the waters of the Euphrates River output the result to be presented to the river directly and without treatment . Samples of wastewater were selected from three cities in the governorate which were Ramadi , Falluja and population compound in the Ameriat al Falluja , the water samples were teasting for chemical elements , then determine the suitability of these waters, according to national standards of the determinants of the protection of rivers from pollution to be used like water irrigation of agricultural land, through the knowledge of the effect of toxic accumulated these elements , and thus determine the appropriate treatment methods for the disposal of environmental pollution that arises through the water discharged into the river, where the recommendation was given the possibility to take advantage of the resulting treated water to irrigate them and the sustainability of desert land by comparing it with the national standards for each area